Tracing the Effect of Functional Rehabilitation for Improving the Quality of Life of Patients with Stroke - Petja KASNAKOVA; Snezhana DRAGUSHEVA; Stefka IVANOVA (Tehran University of Medical Sciences, 2020)
No Abstract